Family Support with Diabetes Management in Type 2 DM: Correlation Study - Ni Wayan Trisnadewi; Ni Wayan Suniyadewi (KHD-Production, 2022)
Diabetes is one of the greatest global health emergencies of the 21st century. The incidence of DM continues to increase every year. Family support is an important aspect in supporting the successful implementation of diabetes management. This study aims to determine the relationship between family support and diabetes management. The design of this research is descriptive correlation with a cross-sectional approach which was carried out from August-October 2021 in Gianyar Regency with a total sample of 207 respondents taken through multistage sampling technique. The results obtained were high dominant family support (51.2%) and dominant diabetes management was in sufficient category (46.4%). The results obtained from the chi-square analysis, the P-value of 0.031, which shows that there is a relationship between family support and diabetes management in type 2 DM patients. The existence of family support will improve diabetes management for type 2 DM patients. support system for patients.